La historia al trasluz: Walter Benjamin y el concepto de imagen dialéctica - De Luelmo Jareño, José María (Escritura e Imagen, 2007)
Despite its great difussion, the writings on photography by Walter Benjamin keep being not well enough understood. The concept of dialectical image, which appears all through his correspondence and his postumous writings, allows them to be much better illuminated and also to give them an internal logics that in fact barely correspond to the usual historiographic parameters. Moreover, in those writings is possible to apreciate the way in which the dialectical image can operate as an instrument for the critical reading of history, that is, as the converter of a narrative guided by private and invariable patterns into a constellation in constant tension.